HUBUNGAN PERSEPSI DAN KIE DENGAN KESEDIAAN MOP DI KECAMATAN PADURESO KABUPATEN KEBUMEN TRIWULAN I TAHUN 2016 - Yulia Nur Azizah; Djoko Nugroho; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Increased men participation in Family Planning and reproductive health are important issues.  Men participation is the responsibility of the involvement and participation of men in family planning, reproductive health and healthy sexual behavior to safe for themselves, spouses and also families. Vasectomy low achievement as a form of lack of men participation in Family Planning. Padureso is one of the districts of 33 districts in Kebumen, it has low and away from target vasectomy achievement (<8.33%), in 2015 amounted to 0%. Vasectomy low achievement caused by negatif perception which is growing among civilan and not implemented IEC.The aim of this research is to analyze the relationship between perceptions and IEC with willingness to have vasectomy in Padureso, Kebumen, Central Java. The type of this research is Explanatory Research with the desain study is Cross Sectional. The population is vasectomy acceptor and a married men who is not an active participant Family Planning amounted 365 people with Simple Random Sampling the results is 68 men. Analysis of the data used univariate analysis, bivariate descriptive and analytic bivariate analysis using statistical test of Rank Spearman with a significance value(α = 5%). The results of univariate analysis showed that the largest percentage is on men with good perception (32,4%), men with less IEC (75,0%), and  men with less willingness to have vasectomy (47,1%). The results of Spearman Rank analysis showed that there is no relationship between perceptions (p value = 0.683; 95% CI = -0.282 - 0.173), IEC (p value = 0.340; 95% CI = -0.344 - 0.123) in men with the willingness to have vasectomy. It is necessary to optimize the IEC as health promotion programs to improve knowledge of couples in obtaining to choose, contraception methods by involving the role of BPPKB in each annual activities suach as promotion, simulation, and interpersonal communication.